Priapism or Prolonged Erection: Is 4 – 6 Hours of Cavernous Ischemia the Time Point of Irreversible Tissue Injury?. (23rd August 2022) - Dekalo, Snir; Stern, Noah; Broderick, Gregory A.; Brock, Gerald
Abstract: Introduction: Ischemic priapism remains a significant cause of morbidity among men. To date, the precise time when penile ischemia results in permanent, non-reversible cavernosal smooth muscle injury, compromising subsequent erectile integrity, remains ill-defined. Objectives: To review the medical literature pertaining to ischemic priapism, focusing on factors that predict the exact timeline of irreversible cavernous tissue injury. Methods: A comprehensive literature search was performed. Our search included both publications on animal models and retrospective clinical series through January 2022. Articles were eligible for inclusion if they contained original data regarding nonreversible tissue injury on histology and/or provided a timeline of erectile function loss or preservation and had full text available in English. Results: Innovative studies in the 1990s using invitro models with strips of rabbit, rat, canine and monkey corpus cavernosal tissue demonstrated that anoxia eliminated spontaneous contractile activity and reduced tissue responsiveness to electrical field stimulation or pharmacological agents. The same models demonstrated that the inhibitory effects of field stimulated relaxation, were mediated by nitric oxide. Subsequent studies using similar models demonstrated that exposure of corpus cavernosum smooth muscle to an acidotic environment impairs its ability to contract. A pH of 6.9 was chosen for these experiments based on a case series of men with priapism, in whom a mean pH of 6.9 was measured in corporal blood after 4–6 hours of priapism. Invivo animal studies demonstrated that after erection periods of 6–8 hours, microscopy shows sporadic endothelial defects but otherwise normal cavernous smooth muscle. In these studies, greater durations of ischemic priapism were shown to result in more pronounced ultrastructural changes and presumably irreversibility. In studies involving human corporal tissues, samples were obtained from men who had experienced priapism for at least 12 hours. Overall, erectile function outcome data is deficient in priapism reporting, especially within treatment windows less than 6 hours. Some reports on ischemic priapism have documented good erectile function outcomes with reversal by 12 hours. Conclusion: Based on our extensive review of animal models and clinical reports, we found that many clinical papers rely on the same small set of animal studies to suggest the time point of irreversible ischemic damage at 4–6 hours. Our review suggests an equal number of retrospective clinical studies demonstrate that ischemic priapism reversed within 6–12 hours may preserve erectile function in many patients.